Effects of Two Oral Hygiene Care Methods on Incidence of Ventilator Associated Pneumonia in Respiratory Care Unit, Suratthani Hospital - Thinhuatoey ฺBenjamard; Songwathana, Praneed; Rakpanusit, Thaparat (Princess of Naradhiwas University Journal, 2019)
Oral care is indicated toVentilator-Associated Pneumonia prevention (VAP). This quasi-experimental research with an interrupted time series design aimed to study the effects of 2 different methods in: 1) oral care to oral hygiene, 2) VAP incident rate, and 3) nurses’ satisfaction. Seventy-two ventilated patients were recruited in the study: 36 subjects in the experimental groupand 36 subjects in the control group. Instruments were: the simplifiedindex for plaque score assessment and the nurses’ satisfaction assessment form, with reliabilityof 0.92 and 0.89, respectively, and the VAP assessment using the Infectious Disease Association of Thailandcriteria.Data analysis used inferential statistics. Results were as follows. Subjects receiving a new oral care presented lower plaque score than those receiving the usual care (p< .05). The VAP incident rate in both groups had no significant difference (5.60:1000 ventilator days, and 5.16:1000 ventilator days; respectively) (p>.05). There were higher nurses’ satisfaction scores on a new oral care than the usual care (p< .05). In conclusion, the new oral care can help a better hygiene for oral cavity and greater nurses’ satisfaction, while theVAP incident rate is not different. Recommendation for nurse administrators and nurses is to imply brushing with 0.12% Chohexidine gluconate twice a day as a VAP prevention mean for ventilated patients.Further study is recommended fordaily oral hygiene testing until patients discharge from the Respiratory Intensive Care Unit